Political Strategies Of Gen Z And Millennial Candidates: A Literature Review On The 2024 Election - Lianda, Febi Dwi; Fernandes, Reno (LANGGAM: International Journal of Social Science Education, Art and Culture, 2025)
The 2024 elections marked a surge in political participation from the younger generation, especially Gen Z and Millennials, who began actively running for the legislature. This research aims to examine the political strategies used by legislative candidates from Gen Z and Millennials through a literature review approach. The focus of the study lies on the political characteristics of the younger generation, the use of social media as a campaign tool, and the challenges and opportunities in actualizing digital political strategies. The findings show that young candidates tend to utilize digital platforms such as Instagram, TikTok, and Twitter to build their image, reach young voters, and strengthen two-way communication. This strategy is considered effective in increasing political engagement, although it still faces obstacles such as digital polarization, limited resources, and social media algorithms. This research contributes to the understanding of the dynamics of youth digital politics and can be a strategic reference for political actors and researchers in the field of contemporary politics.